Descriptive analysis of extra-curricular program outcome attainment: a case study of Universiti Malaysia Pahang - Siti Zanariah, Satari; Nor Alisa, Mohd Damanhuri; Rozieana, Khairuddin; Roslinazairimah, Zakaria (Akademi Sains Malaysia, 2019)
This study presents the descriptive analysis of students’ performance in extra-curricular activities at Universiti Malaysia Pahang (UMP) for all bachelor degree students from year 2015 to 2018. A new reporting mechanism and formula, known as Extra-Curricular Cumulative Grade Point Average (XCGPA), is proposed for assessing the students’ involvement in extra-curricular program organised by UMP. The data analysed is merit scores obtained by students from joining the extra-curricular activities during their study period in UMP. The merit scores are categorized into involvement, role and achievement with different weightages based on students’ level of involvement. The total merit scores from each category will be mapped between the intended core values and the targeted attributes. There is a threshold merit score for each attribute to be obtained by the student per semester and for the study duration. Then, the percentage score for each attribute is calculated and classified according to six Student Personality Trait Classifications. The students’ profile is developed and the attainment for each attribute is presented by a spider web.